ANALISIS PENGARUH STOCK SPLIT TERHADAP LIKUIDITAS SAHAM DAN ABNORMAL RETURN SAHAM PADA MASA PANDEMI COVID-19 - Sitiyarningrum, Vivi Aditya; SS, Vietha Devia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Stock split is a policy applied by public companies in which the number of issued stocks is increased so that more investors can buy them. The policy can help companies increase their liquidity and their investors’ gain through abnormal return. The application of it during the Covid-19 pandemic is appealing and important to study as the widespread is a substantial incidents with global impact. Investors can use the derived information to consider their investment decisions. This research was conducted on the stocks of three financial companies listed on the IDX during the 2020-2021 period. Here paired sample t-test was used to identify differences in stock liquidity ad abnormal return before and after stock split had been implemented. The observation period was five days prior and after the stock split and one day during the announcement, resulting in 11 days in total. This study finds that, before and after the split, the stock liquidity of BBCA was significantly different, but it was not the case for AMOR and SRTG, while the abnormal return had no significant difference.